Category shift in the translation of trump's speech recognizing Jerusalem as the capital of Israel - Muhamad Ihsan Baihaqi (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2021)
wt,1/adil,c.1